Therapeutic benefits of lower limb prostheses: a systematic review - Elke Lathouwers; María Alejandra Díaz; Alexandre Maricot; Bruno Tassignon; Claire Cherelle; Pierre Cherelle; Romain Meeusen; Kevin De Pauw (Journal of NeuroEngineering and Rehabilitation, 2023)
Abstract Background Enhancing the quality of life of people with a lower limb amputation is critical in prosthetic development and rehabilitation. Yet, no overview is available concerning the impact of passive, quasi-passive and active ankle–foot prostheses on quality of life. Objective To systematically review the therapeutic benefits of performing daily activities with passive, quasi-passive and active ankle–foot prostheses in people with a lower limb amputation. Methods We searched the Pubmed, Web of Science, Scopus and Pedro databases, and backward citations until November 3, 2021. Only English-written randomised controlled trials, cross-sectional, cross-over and cohort studies were included when the population comprised individuals with a unilateral transfemoral or transtibial amputation, wearing passive, quasi-passive or active ankle–foot prostheses. The intervention and outcome measures had to include any aspect of quality of life assessed while performing daily activities. We synthesised the participants’ characteristics, type of prosthesis, intervention, outcome and main results, and conducted risk of bias assessment using the Cochrane risk of bias tool. This study is registered on PROSPERO, number CRD42021290189. Results We identified 4281 records and included 34 studies in total. Results indicate that quasi-passive and active prostheses are favoured over passive prostheses based on biomechanical, physiological, performance and subjective measures in the short-term. All studies had a moderate or high risk of bias. Conclusion Compared to passive ankle–foot prostheses, quasi-passive and active prostheses significantly enhance the quality of life. Future research should investigate the long-term therapeutic benefits of prosthetics devices.